Diagnosa Kebuntingan Dini Melalui Pengukuran Hormon Progesterone Pada Air Susu Kambing Untuk Meningkatkan Produksi ternak = Early Pregnancy Diagnosis By Assesing Milk Progersterone Level On Goats To Increase Livestock Pr - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT: After studying the main techniques used to diagnose pregnancy on goats the authors concluded that assesing milk Progesterone levels has an advantage in this species. The experiment was conducted on 560 female goats of various stocks and ages. Milk samples were taken 21 to 23 days after natural mating or artificial insemination. Following a hormonal Radio Immunological Assay, the results were as follows : - For goats presumed pregnant : 87.7% accuracy for pregnancy. - For goats presumed non pregnant : 97.7% accuracy for non-pregnancy. Because of its earliness and reliability, this technique, either in conjuction or not with Echotomography/Ultrasonography offer a promising possibility from a practical point of view.